Culturally Sensitive Care for Asian Immigrants: Home Healthcare Perspectives. (October 2017) - Ko, Arthur; Turner, Jill
Abstract : The number of Asian immigrants has risen dramatically in recent decades, making them the fastest growing immigrant group in the United States. Home healthcare clinicians are expected to meet the healthcare needs of patients regardless of their ethnic or cultural background, but this can be challenging without a basic understanding of the patient's culture. This article is intended to provide information about the cultural traditions and health conditions clinicians may encounter when caring for patients and families who have immigrated to the United States from the top five Asian countries as determined by the U.S. Census, and concludes with resources that home healthcare clinicians can utilize when engaging in patient education.